2014
DOI: 10.1177/1457496913512829
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of patient satisfaction and donor-site morbidity after different types of breast reconstruction

Abstract: Background and Aims: breast reconstruction has been shown to improve quality of life. However, factors involved in long-term patient satisfaction are largely unknown. Our aim was to evaluate patient satisfaction and donor-site morbidity in five types of breast reconstruction. Results: there were 257 patients identified, of whom, 126 responded to the survey (17 implant, 5 latissimus dorsi + implant, 64 latissimus dorsi, 22 transverse rectus abdominis musculocutaneous, and 18 deep inferior epigastric perforator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
8
0
2
Order By: Relevance
“…A total of 18 articles were ultimately included in this systematic review. 9 14 , 21 32 Overall risk of bias was low for 5 and moderate for 11 studies ( see Supplemental Digital Content 1, http://links.lww.com/PRSGO/B491 ). Fifteen articles assessed safety, 9 11 , 13 , 14 , 21 30 , 32 and 8 provided patient-reported outcomes ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 18 articles were ultimately included in this systematic review. 9 14 , 21 32 Overall risk of bias was low for 5 and moderate for 11 studies ( see Supplemental Digital Content 1, http://links.lww.com/PRSGO/B491 ). Fifteen articles assessed safety, 9 11 , 13 , 14 , 21 30 , 32 and 8 provided patient-reported outcomes ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Restoration of psychological well‐being is a key objective for postmastectomy women undergoing breast reconstruction. Therefore, patient satisfaction (which reflects the patient'sassessment of the achievement of personal benefits of the procedure) is an important marker of surgical success in breast reconstruction, as the overall goal is to satisfy patients with respect to improvement in the appearance of their breasts and psychosocial functioning . Patient satisfaction measures have been reported as a primary and useful source of feedback within healthcare services and many patients report high levels of satisfaction following breast reconstruction .…”
Section: Introductionmentioning
confidence: 99%
“…However, the value of distinguishing between satisfaction with the appearance of the breasts (eg, size, shape, and symmetry) and satisfaction with the overall outcome (eg, overall evaluation of surgery, expectations, and decision regret) is under‐recognised within the field of psycho‐oncology. Moreover, a central rationale in the majority of healthcare interventions is the improvement in one or more aspects of a patient's quality of life, and contemporary literature indicatesimproved quality of life following post‐mastectomy breast reconstruction …”
Section: Introductionmentioning
confidence: 99%
“… 12 – 14 In reconstructive breast surgery, patient expectations play a critical role because success hinges on patient satisfaction, though a clear relationship between expectations and outcomes has not been proven. 15 Hoch et al 16 found that clinical factors such as operation type, complications, and revision rate were not predictive of long-term satisfaction in breast reconstruction and suggest redirecting focus to patient education. Our findings provide data necessary to correct misguided expectations, thereby optimizing patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%